Risk of tin whiskers in the nuclear industry. (February 2018) - Huang, Chien-Ming; Nunez, Daniel; Coburn, James; Pecht, Michael
Abstract: This paper identifies tin whisker-related faults and failures that have been reported in the nuclear power industry and discusses the unique reliability and safety challenges faced by nuclear power plants. Specific areas of concern include supply chain and parts selection, fault reporting, regulations and measurement techniques, and the adoption of lead-free legislation. Issues of parts availability and obsolescence are also discussed. The paper concludes with strategies and recommendations that can be used to mitigate and manage risks from tin whiskers in the nuclear industry.